Chemo-proteomics exploration of HDAC degradability by small molecule degraders. Issue 10 (21st October 2021) - Xiong, Yuan; Donovan, Katherine A.; Eleuteri, Nicholas A.; Kirmani, Nadia; Yue, Hong; Razov, Anthony; Krupnick, Noah M.; Nowak, Radosław P.; Fischer, Eric S.
Summary: Targeted protein degradation refers to the use of small molecules that recruit a ubiquitin ligase to a target protein for ubiquitination and subsequent proteasome-dependent degradation. While degraders have been developed for many targets, key questions regarding degrader development and the consequences of acute pharmacological degradation remain, specifically for targets that exist in obligate multi-protein complexes. Here, we synthesize a pan-histone deacetylase (HDAC) degrader library for the chemo-proteomic exploration of acute degradation of a key class of chromatin-modifying enzymes. Using chemo-proteomics, we not only map the degradability of the zinc-dependent HDAC family identifying leads for targeting HDACs 1–8 and 10 but also explore important aspects of degrading epigenetic enzymes. We discover cell line-driven target specificity and that HDAC degradation often results in collateral loss of HDAC-containing repressive complexes. These findings potentially offer a new mechanism toward controlling chromatin structure, and our resource will facilitate accelerated degrader design and development for HDACs. Graphical abstract: Highlights: Pan-HDAC degrader library enabled chemo-proteomics map of HDAC degradability HDAC degradation results in degradation of HDAC-containing repressive complexes Cell line-dependent HDAC isoform specificity Abstract : Xiong et al. report the design and synthesis of a diverse multi-targeted library of HDAC degraders and assess their activity in cells. The findings provide a roadmap for future design of HDAC-targeted degraders and reveal important insights regarding the biological role of this epigenetic family of enzymes.